2008
DOI: 10.1213/ane.0b013e3181683d37
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane-Mediated Activation of p38-Mitogen-Activated Stresskinase is Independent of Apoptosis in Jurkat T-Cells

Abstract: Sevoflurane is a specific activator of the apoptosis signal-regulating kinase-1-, MKK3/MKK6-p38 MAP kinase cascade in Jurkat T-cells. Our data suggest that sevoflurane-induced p38 activation is not affected by caspase activation. Furthermore, sevoflurane-induced apoptosis is not dependent on p38 MAP kinase activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 54 publications
(44 reference statements)
1
18
1
Order By: Relevance
“…Our results are not consistent with their results, possibly due to our use of a different category of cell line (Loop and Roesslein [14,15] used human T lymphocytes and Jurkat T-cells). However, the cell line investigated in this study is a human lung adenocarcinoma A549 cell line.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results are not consistent with their results, possibly due to our use of a different category of cell line (Loop and Roesslein [14,15] used human T lymphocytes and Jurkat T-cells). However, the cell line investigated in this study is a human lung adenocarcinoma A549 cell line.…”
Section: Discussioncontrasting
confidence: 99%
“…Loop and Roesslein [14,15] found that sevoflurane activates the p38 MAPK signaling pathway and increases phosphorylation of p38 MAPK. Our results are not consistent with their results, possibly due to our use of a different category of cell line (Loop and Roesslein [14,15] used human T lymphocytes and Jurkat T-cells).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the sevoflurane group, the cells were put in a 1.2 L sealed container, which was connected to an anaesthesia apparatus (Dräger Fabius GS) that had a sevoflurane vapor (Dräger Vapor 2000), and could consistently supply 8% sevoflurane, air and 5% CO 2 . The container was placed into a 5% CO 2 incubator, and the cells were cultured for 24 h at 37 o C. The concentration and duration of sevoflurane administration were selected based on our preliminary experiments and previous reports (Matsuoka et al, 2001;Loop et al, 2005;Roesslein et al, 2008). In the propofol + sevoflurane groups, the cells were cultured in RPMI 1640 media containing propofol at concentrations of 5, 10, 25 or 50 µg/mL, and 15 min later the cells were exposed to 8% sevoflurane as above for 24 h at 37 o C in a 5% CO 2 incubator.…”
Section: Groups and Treatmentsmentioning
confidence: 99%
“…Sevoflurane induces apoptosis in various types of human cells including peripheral polymorphonuclear neutrophils (Wong et al, 2006), primary T lymphocytes (Loop et al, 2005), Jurkat T cells (Loop et al, 2005;Roesslein et al, 2008), and other cells (Kvolik et al, 2005). Its pro-apoptotic activity can be explained by its ability to increase disruption of the mitochondrial membrane (which reduces the membrane potential, ∆Ψm), activate caspase-3, and release cytochrome c (Loop et al, 2005), or to trigger the formation of peroxynitrite and increase production of reactive oxygen species (ROS) (Wong et al, 2006), or to mediate activation of p38-mitogen-activated protein kinase cascades (Roesslein et al, 2008).…”
Section: Introductionmentioning
confidence: 99%